A fire-retarding electrolyte using triethyl phosphate as a solvent for sodium-ion batteries. Issue 4 (15th December 2021) - Du, Kang; Wang, Chen; Balaya, Palani; Gajjela, Satyanarayana Reddy; Law, Markas
Abstract : Here, we introduce a fire-retarding electrolyte for sodium-ion batteries using fire-retardant triethyl phosphate (TEP) as a solvent. 3% vinylene carbonate (VC) is added to enhance its stability. Abstract : We introduce a fire-retarding phosphate-based electrolyte, 1 M NaBF4 in triethyl phosphate with 3% vinylene carbonate as an SEI-forming additive, for sodium-ion batteries. With this electrolyte formulation, we achieved stable cycling performance with a capacity of 80.5 mA h g −1 and a retention of 77.8% after 200 cycles in the Na-ion full cell of Na3.2 V1.8 Zn0.2 (PO4 )3 vs. hard carbon.